Bone Minimodeling, a Special Modeling Pattern and Potential as Therapeutic Target for Osteoporosis - Li, X.; Zhang, J.; Wang, X. (Current Molecular Medicine, 2018)
The concept of minimodeling is defined as a kind of focal bone formation that features the absence of preceding bone absorption by osteoclasts. In the process of minimodeling, osteogenetic and osteoclastic activities are decoupled. Linear boundary between old bone and new bone can be discovered. Frost et al. presumed that minimodeling in trabeculae can continue throughout life. The concept of minimodeling is not new, however its function and nature are still imperfectly understood. Our review will focus on minimodeling-based formation in 5 aspects below: 1. compare the minimodeling with remodeling regarding 10 items; 2. describe the histological observation to characterize remodeling and minimodeling formation sites; 3. present evidence of bone anabolic agents which start bone minimodeling; 4. discuss the mechanism and target cells involved in bone minimodeling; 5. interpretate the increased osteogenic potential and trabecular connectivity with minimodeling-based formation; 6. Depict modeling patterns of the bone implant interface and peri-implant osteogenesis in osteoporosis. This review provides an in-depth knowledge regarding minimodeling comprehensively and its potential contributions in skeletal homeostasis and application prospect in improving the success rate of dental implant in osteoporosis.
Keywords: osteointegration